HUBUNGAN ANTARA KETERAMPILAN KOMUNIKASI DENGAN KECEMASAN BERBICARA DI DEPAN UMUM - Ilyas, Asmidir; ., Marjohan (Universitas Negeri Padang, 2013)
Communication skills are essential for students, where is communication skills is an abilityfor extending message exactly to others and students be able to perform in front of public. Infact thatthere is a student who tends to have less verbal, fail to express thoughts and ideas in his mind, getanxious on public speaking, feel heart beats very fast and perspire just before starting a speech, afeeling of helplessness building up when speaking on public speaking. This study aims to know therelationship between communication skills with public speaking anxiety. Correlation Productmoment analysis showed that there was a significant correlation between skills communication andpublic speaking anxiety r = -0,785 0,01. The result showed that there was a negative correlationalbetween skills communication with public speaking anxiety. It means the higher students skillscommunication then their public speaking anxiety level becomes lower and contrary, lower studentsskills communication then their public speaking anxiety level become higher.